Politeness Strategies in Netizens’ Comments on Public Figures: A Case Study on Fuji An’s TikTok - Fahmia (Universitas Islam Tribakti Lirboyo Kediri, 2025)
This study investigates the politeness strategies used by Indonesian netizens in TikTok comments directed at public figure Fuji An. As social media becomes a dominant space for public discourse, understanding how politeness and impoliteness are linguistically expressed is essential. Using a descriptive qualitative approach, the research analyzed 40 purposively selected comments from one of Fujian’s TikTok videos. The comments were categorized using Brown and Levinson’s politeness theory, which includes bald on record, positive politeness, negative politeness, and off record strategies. The findings show that positive politeness was the most frequently used strategy, indicating strong affective support from followers. However, instances of impoliteness and verbal attacks, particularly those targeting religious aspects and personal identity, were also present. These results suggest that TikTok comment sections represent a complex interactional space where empathy, criticism, and hostility coexist. The study concludes that digital politeness strategies are shaped by cultural proximity, public perception, and platform dynamics. The findings imply the need for greater digital literacy and ethical awareness to foster respectful online communication, particularly toward local public figures in Indonesia.